2007
DOI: 10.1007/s00542-006-0368-8
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of Si-DLC film and its microstructural, tribological and corrosion properties

Abstract: Silicon-incorporated diamond-like carbon (Si-DLC) films were deposited using a bipolar-type plasma based ion implantation and deposition technique, and the effects of Si-incorporation on the microstructural, tribological, anti-corrosion and lubricant bonding properties of the Si-DLC films were investigated. The analysis of Raman spectroscopy exhibited that the sp 3 bonds in the DLC film increase due to Si addition. XPS analysis revealed that a thick oxide layer exists on the Si-DLC film surfaces. These explain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 12 publications
1
24
0
Order By: Relevance
“…11, revealed an apparent shift of Si2p peak from 100.3 to 102.3 eV, indicating that some SiC was converted to SiO x during the sliding friction. Hence, superior tribological performances of the as-fabricated a-C:Si and a-C:Si:Al coatings should be attributed to the formation of low shear strength colloidal silica (or SiO x (OH) y ) tribofilm by the tribochemical reaction of Si or SiC with H 2 O molecule on contact area under high relative humidity conditions [13,16,17]. Moreover, a-C:Si:Al coating presented better tribological performances compared with a-C:Si under high relative humidity becauseof its good combining mechanical properties.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…11, revealed an apparent shift of Si2p peak from 100.3 to 102.3 eV, indicating that some SiC was converted to SiO x during the sliding friction. Hence, superior tribological performances of the as-fabricated a-C:Si and a-C:Si:Al coatings should be attributed to the formation of low shear strength colloidal silica (or SiO x (OH) y ) tribofilm by the tribochemical reaction of Si or SiC with H 2 O molecule on contact area under high relative humidity conditions [13,16,17]. Moreover, a-C:Si:Al coating presented better tribological performances compared with a-C:Si under high relative humidity becauseof its good combining mechanical properties.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, many researchers have devoted to the preparation of carbon-based coatings by doping additional elements to overcome those drawbacks. Among those studies, silicon incorporation in the carbon-based coatings has been widely studied and was reported as being effective in improving tribological performances in ambient humid air and water conditions by alleviating internal stress and preventing generation of micro-cracks and partial ruptures in wear tracks [13][14][15][16]. Moreover, other explanations for that effect have been offered, including the formation of SiO 2 at the frictional interface and an increase in sp 3 hybridization resulting in a less graphitic carbon [17][18][19][20].…”
Section: Introductionmentioning
confidence: 96%
“…Parameter describing the nature of sp 2 bond are the ratio of peaks intensities [19,20]. If the silicon content was higher than the ID/IG ratio would be smaller [17,21]. The ID/IG ratio for DLC:Si/AlCrN in this case is 0.73.…”
Section: Resultsmentioning
confidence: 84%
“…8, have confirmed that an apparent shift of Si2p peak from 100.3 eV to 102.7 eV as the relative humidity increased from R.H. 5% to 90%. Hereby, under high relative humidity conditions, the improved tribological performances of as-fabricated a-C:Si:Al coating should be attributed to the formation of low shear strength colloidal silica (or SiO x (OH) y ) tribo-film by the tribo-chemical reaction of Si or SiC with H 2 O molecule on contact surfaces in the case of Si 3 N 4 , SiO 2 and GCr15 counterparts [11,14,15]. In addition, the Si-based ceramics showed that the chemical resultant such as SiO 2 or SiO x would be formed on the friction contact surface supposed as reaction (1) [34,35].…”
Section: Discussionmentioning
confidence: 95%
“…Consequently, many researchers have devoted to the preparation of DLC coatings by doping additional elements to overcome high tribological moisture sensitivity. Among those studies, Si incorporation in the DLC coatings has been widely studied and was confirmed as being effective in improving tribological moisture sensitivity by alleviating internal stress and preventing generation of micro-cracks and partial ruptures in wear tracks [11][12][13][14]. Moreover, other explanations for that effect have been offered, including the formation of SiO 2 at the frictional interface and an increase in sp 3 hybridization resulting in a less graphitic carbon [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%